The Effects of Social Media on the Dynamics of Identity: Discourse, Interaction and Digital Traces - Heike Baldauf; Christine Develotte; Magali Ollagnier-Beldame (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
This paper introduces the journal's special issue concerning identity construction in social media. While considering social media, we examine how (and if) its use changes the dynamics of identity: constructing or shaping the identity, negotiating it, etc. In other words, what do social media "do" to dynamics of identity? With our multi-disciplinary background (philosophy, linguistics, cognitive sciences), we will seek to answer this question at least partially by first explaining what we mean by dynamics of identity (part 1) and how we study social media in terms of interactivity and discursiveness and by the digital traces they leave behind (part 2). Thirdly, we will examine identity construction with the temporal, spatial and otherness dimensions, which are the three fundamental aspects of human interaction (part 3).